2013
DOI: 10.3389/fimmu.2013.00207
|View full text |Cite
|
Sign up to set email alerts
|

Liver FOXP3 and PD1/PDL1 Expression is Down-Regulated in Chronic HBV Hepatitis on Maintained Remission Related to the Degree of Inflammation

Abstract: Background and Aim: T cell expression of PD1 and inhibition of T effector cells by Foxp3+-T regulatory cells are among the most powerful mechanisms for achieving a balanced immune response. Our aim was to investigate, how liver FOXP3 and PD1/PDL1 expression is regulated in chronic HBV hepatitis (CHB) on maintained long-term remission in comparison with active disease, and whether they are correlated to the expression of pro- and anti-inflammatory cytokines and apoptosis mediators, along with the degree of hist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0
5

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 38 publications
3
22
0
5
Order By: Relevance
“…First-strand cDNA synthesis was carried out using the Transcriptor first-strand cDNA synthesis kit (Roche, San Francisco, CA). Primers specific for PD-L1 (15) and RPL13a (16) were used for amplification, and results were analyzed using the ⌬⌬C T method. Gene expression is represented as fold change in virusinfected versus mock-infected cells or cytokine-treated versus mock-infected cells.…”
Section: Flow Cytometry (Facs)mentioning
confidence: 99%
“…First-strand cDNA synthesis was carried out using the Transcriptor first-strand cDNA synthesis kit (Roche, San Francisco, CA). Primers specific for PD-L1 (15) and RPL13a (16) were used for amplification, and results were analyzed using the ⌬⌬C T method. Gene expression is represented as fold change in virusinfected versus mock-infected cells or cytokine-treated versus mock-infected cells.…”
Section: Flow Cytometry (Facs)mentioning
confidence: 99%
“…It remains unclear, however, whether this decrease in PD-1 expression is a direct effect of the drugs on this molecule, or it is secondary to the decrease of the in-vivo inflammatory milieu under laboratory conditions. The former hypothesis is supported by the finding of a direct association between increase in PD-1 mRNA levels and intensity of liver inflammation in chronic hepatitis B [40].…”
Section: Discussionmentioning
confidence: 78%
“…In this most common clinical case scenario, we have found that the expression of FOXP3, IL10, TGFB1, PD1, PDL1, FASL, and CD8 was significantly downregulated in the remission state. (4) Moreover, FOXP3, PD1, PDL1, and CD8 transcripts were positively correlated with the intensity of liver inflammation. However, it is still uncertain whether the expression of PDL1 on hepatocytes truly contributes to the development of T-cell exhaustion or whether it is a homoeostatic mechanism that dampens the inflammatory reaction.…”
Section: Checkpoint Modulation In Chronic Hepatitis B: From Hypothesimentioning
confidence: 94%
“…However, it is still uncertain whether the expression of PDL1 on hepatocytes truly contributes to the development of T-cell exhaustion or whether it is a homoeostatic mechanism that dampens the inflammatory reaction. (4) Therefore, the targeting of Tregs and/or PD1/ PDL1 pathway in the acute, or the early chronic HBV infection setting, may trigger autoimmune phenomena or increase immune-mediated liver damage.…”
Section: Checkpoint Modulation In Chronic Hepatitis B: From Hypothesimentioning
confidence: 99%